ATTITUDE OF EMPLOYEES TOWARDS CHANGE INITIATIVES AS INFLUENCED BY COMMITMENT AND JOB SATISFACTION: THE CASE OF SELECTED HIGHER EDUCATION INSTITUTIONS IN ETHIOPIA - Wedajo, Megersa; Chekole, Belay (Journal of process management and new technologies, 2020)
The purpose of this study is to examine the influence of organizational commitment and job satisfaction on attitudes of employees toward change initiatives in public universities in Ethiopia. Self-Administered questionnaires were prepared and distributed to 200 randomly selected teachers in selected universities via e-mail addresses. Correlation and Regression analysis was conducted to see the influences of the two variables. The results revealed that employees ` general attitudes towards change initiatives is influenced by Job satisfaction (p0.05).
Keywords: Change Initiatives, Attitude towards change, employee commitment, Job satisfaction, Higher Education Institutions